A rapid preparation method and application of sulfur-host lithium-sulfur battery positive electrode material

Sulfur-hosted lithium-sulfur battery cathode materials are prepared through Joule heat treatment technology to form a homologous heterojunction structure of Mn3O4/MnS, which solves the problems of shuttle effect and low preparation efficiency of lithium-sulfur batteries, achieving improved performance and reduced energy consumption.

CN118825245BActive Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411264337.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-21
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Lithium sulfur batteries have a shuttle effect during charging and discharging, resulting in poor comprehensive performance, and low efficiency and high energy consumption in the preparation process of traditional composite materials.

Method used

Joule heat treatment technology is used to prepare sulfur-hosted lithium-sulfur battery cathode materials. Through rapid heating and heat preservation under nitrogen protection, a homologous heterojunction structure of Mn3O4/MnS is formed. Combined with carbon materials with good conductivity, the sulfur redox kinetics are optimized.

Benefits of technology

Significantly suppresses the shuttle effect of lithium-sulfur batteries, improves volumetric energy density, cycle life and rate capability, and has high preparation efficiency and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825245B_ABST
    Figure CN118825245B_ABST
Patent Text Reader

Abstract

The invention discloses a rapid preparation method and application of a sulfur-host lithium-sulfur battery positive electrode material, which belongs to the technical field of lithium-sulfur battery positive electrode material preparation. The invention first uses the metal organic framework material ZIF‑8 as a template, undergoes Joule heat treatment, and rapidly synthesizes a porous carbon material, then impregnates a manganese salt in an ethanol solution, reacts with thioacetamide through a Joule heat-driven solid phase reaction, and controls the heating and cooling atmosphere to rapidly prepare a sulfur-host lithium-sulfur battery positive electrode material. The Mn3O4 / MnS heterostructure in the sulfur-host lithium-sulfur battery positive electrode material creates an interface with high activity, which can enhance the chemical adsorption of polysulfides and their catalytic conversion, thereby significantly promoting the kinetic process of sulfur redox reactions and improving the overall performance of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rapid preparation method and application of a sulfur-host lithium-sulfur battery positive electrode material, belonging to the technical field of lithium-sulfur battery positive electrode material preparation. Background Art

[0002] Against the backdrop of growing global energy demand, excessive use of fossil fuels has led to numerous environmental challenges, driving renewable energy to become a key area supporting modern life. Due to the geographical and temporal mismatch between energy supply and demand, energy storage technology has become a core component of the new energy system. As a new energy storage technology, lithium-sulfur batteries have gradually become an advanced battery system with broad research and commercialization prospects due to their high theoretical capacity (1675 mAh / g) and energy density (2600Wh / kg), which far exceeds existing lithium-ion batteries, and their environmental protection and low cost advantages. However, the commercialization of lithium-sulfur batteries is still limited by several technical barriers, such as the poor electrochemical rate performance and low conductivity of lithium polysulfides produced during the elemental sulfur redox reaction. Another challenge in the development of lithium-sulfur batteries is the dissolution of lithium polysulfides in the electrolyte, which leads to the shuttle effect and the continuous loss of active materials. To solve these problems, it is imperative to develop and design efficient and stable sulfur-hosted lithium-sulfur battery cathode materials.

[0003] The Chinese invention patent document with publication number CN110600690A discloses a zeolite imidazole framework-derived nitrogen-doped hierarchical porous carbon @ manganese tetraoxide @ carbon / sulfur (N-HPC@Mn3O4@NC / S) and its preparation method and application. The method first obtains N-HPC by heat treatment at high temperature of 900-950°C, then obtains N-HPC@Mn3O4 by hydrothermal reaction, then encapsulates dopamine, and finally obtains N-HPC@Mn3O4@NC sulfur host material by carbonization treatment at 600-800°C under argon atmosphere. This method requires cumbersome wet chemical and heat treatment steps, which consumes a lot of time and energy. In addition, the patent essentially improves the conductivity, inhibits the "shuttle effect" of lithium polysulfide, and inhibits the volume expansion of sulfur during charging and discharging through the composite of carbon material and Mn3O4, thereby improving the performance of lithium-sulfur batteries, but does not regulate the optimization behavior of Mn3O4 on sulfur redox kinetics.

[0004] The Chinese invention patent with publication number CN109309217A discloses a method for preparing positive electrode materials for lithium-sulfur batteries. The method comprises the following steps: subjecting graphene or carbon nanotubes to a high-temperature hydrothermal reaction in an acidic solution of potassium permanganate and hydrochloric acid to obtain a graphene or carbon nanotube composite material with manganese oxide loaded on the surface; calcining the composite material at a high temperature to obtain a carbon-based manganese oxide composite material; and reacting and doping the carbon-based manganese oxide composite material with sublimated sulfur to obtain a graphene / carbon nanotube@Mn3O4@S composite material, which is applied to positive electrode materials for lithium-sulfur batteries. This preparation method requires the use of an acidic solution to treat graphene or carbon nanotubes, and the discharge of the acidic solution can easily cause environmental pollution; the composite material of this method does not involve homologous heterojunctions and multi-level pore structures (the combination of organic ligands and metal cations will obtain microporous materials, and the microporous materials will obtain multi-level pore structures after post-treatment), and also requires high-temperature hydrothermal reactions, which has high energy consumption; in addition, the traditional tubular furnace calcination method can easily cause the collapse of the pore structure, that is, the pore size range becomes smaller, which in turn leads to poor performance of the lithium-sulfur battery; the essence of this method is to obtain a carbon material surface loaded with metal oxides for the positive electrode of a lithium-sulfur battery.

[0005] The Chinese invention patent with publication number CN115084480A discloses a metal oxide-metal sulfide heterojunction material and its preparation method and application. The method is to obtain a gel by a high-temperature hydrothermal method in ethylene glycol containing citric acid, and the gel is calcined in a tubular furnace to obtain a metal oxide. The metal oxide and sublimated sulfur are reacted in a closed manner at a high temperature to obtain a sulfur-doped metal oxide, namely Na 0.67 Ni x Mn 1-x O2@S composite; the composite is used as the negative electrode, and is assembled into a button battery with the electrolyte, positive electrode, etc. After multiple charge and discharge, a metal oxide-metal sulfide heterojunction, namely Na 0.67 Ni x Mn 1-x -MnS2-Ni3S4; disassemble the button battery, wash it several times, and take out the Na 0.67 Ni x Mn 1-x -MnS2-Ni3S4, which is the required negative electrode material for lithium-sulfur batteries. This method requires multiple charging and discharging of sulfur-doped metal oxides to obtain metal oxide-metal sulfide heterojunctions, which wastes electricity; this method also requires disassembly of button batteries to obtain negative electrode materials for lithium-sulfur batteries with metal oxide-metal sulfide heterojunctions. In the industrial process, battery disassembly requirements are extremely high (prone to fire or explosion), and the operation process is cumbersome; negative electrode materials for lithium-sulfur batteries with metal oxide-metal sulfide heterojunctions need to be installed twice to obtain the desired lithium-sulfur batteries; in addition, the calcination method of the traditional tubular furnace easily leads to the collapse of the pores (the pore size becomes smaller), resulting in poor performance of lithium-sulfur batteries. Summary of the invention

[0006] The purpose of the present invention is to provide a rapid preparation method for sulfur-host lithium-sulfur battery cathode materials, which can solve the problem of poor overall performance caused by the shuttle effect during the charge and discharge process of lithium-sulfur batteries and the problem of low efficiency and high energy consumption in the preparation process of traditional composite materials. The method can inhibit the "shuttle effect" of lithium-sulfur batteries, optimize the sulfur redox kinetics promoted by metal compounds, and greatly improve the volume energy density, cycle life, and rate capability of lithium-sulfur batteries.

[0007] To achieve this object, the technical solution of the present invention is:

[0008] A method for rapidly preparing a sulfur-host lithium-sulfur battery cathode material comprises the following steps:

[0009] (1) Mixing a zinc nitrate methanol solution and a 2-methylimidazole methanol solution, subjecting the mixture to ultrasonic reaction at room temperature for 4-8 hours, and then centrifuging, washing, and drying to obtain a first precursor;

[0010] (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment under a nitrogen protective atmosphere to obtain a second precursor;

[0011] (3) mixing a manganese source with ethanol to prepare a manganese-containing solution; adding the second precursor to the manganese-containing solution, stirring and reacting at 60-90° C. until completely dried, to obtain a third precursor;

[0012] (4) The third precursor and thioacetamide are placed on the left and right ends of the groove of the graphite sample stage of the Joule heating device, respectively, and Joule heat treatment is performed under a nitrogen protective atmosphere. After reaching the target temperature, the temperature is kept for 5-15 seconds, and then the temperature is switched to an air atmosphere for Joule heat treatment to obtain a sulfur-host lithium-sulfur battery positive electrode material.

[0013] Furthermore, in step (1), the concentration of the zinc nitrate solution is 20-40 mM, and the concentration of the 2-methylimidazole solution is 80-100 mM.

[0014] Furthermore, in step (1), the washing conditions are: washing with methanol three to five times; and the drying conditions are: drying temperature 60-100° C., and drying time 4-8 h.

[0015] Furthermore, in step (2), the Joule heat treatment temperature is 800-1000°C, the heating rate is 1000-3000°C / s, and the number of Joule heat treatments is 2-10 times. The Joule heat treatment is heating from room temperature to the target temperature in a nitrogen insulation atmosphere, then keeping the temperature for reaction, and finally naturally cooling to room temperature in an air atmosphere, which is represented as one time.

[0016] Furthermore, in step (3), the manganese source is manganese chloride tetrahydrate or manganese nitrate hexahydrate; the concentration of the manganese-containing solution is 10-30 mM; and the amount of the second precursor added is 0.5-1 g:10 ml based on the amount of ethanol in the manganese-containing solution.

[0017] Furthermore, in the step (4), the usage ratio of the third precursor to thioacetamide is 0.1 g: 0.1-1 g.

[0018] Furthermore, in step (4), the Joule heat treatment conditions are: heat treatment temperature 500-1000°C, heating rate 1000-3000°C / s, and Joule heat treatment times 1-5 times. The Joule heat treatment is heating from room temperature to the target temperature under a nitrogen atmosphere, and then naturally cooling to room temperature under an air atmosphere, which is represented as one time.

[0019] Another object of the present invention is to provide an application of a sulfur-host lithium-sulfur battery positive electrode material prepared by the above method, which is applied to the positive electrode of a lithium-sulfur battery.

[0020] The beneficial effects of the present invention are:

[0021] (1) Compared with the traditional calcination method, the Joule heat treatment technology used in the present invention has simple equipment operation, high efficiency and low energy consumption in preparing sulfur-host lithium-sulfur battery positive electrode materials, while ensuring that the sulfur host material of the lithium-sulfur battery has excellent electrochemical properties.

[0022] (2) The present invention causes an extreme environment of high temperature and high pressure during the rapid heating and heat preservation process using a Joule heat device under a nitrogen protective atmosphere, thereby promoting the rapid formation of MnS, while the cooling process of the air atmosphere promotes partial oxidation of MnS to form a Mn3O4 / MnS homo-heterojunction; by constructing a Mn3O4 / MnS homo-heterojunction structure through interface engineering, the Mn3O4 surface in the homo-heterojunction structure has strong polarity and can provide a variety of polar active sites, which helps to accelerate the conversion of polysulfides, thereby inhibiting the "shuttle effect" of lithium-sulfur batteries; the Mn3O4 / MnS homo-heterojunction structure is also compounded with a carbon material with good conductivity, which can not only exert the synergistic effect of the carbon material and the metal compound, but also optimize the sulfur redox kinetic behavior promoted by the metal compound, greatly improving the volume energy density, cycle life, and rate capability of lithium-sulfur batteries, and has broad industrial prospects.

[0023] (3) The sulfur-host lithium-sulfur battery positive electrode material prepared by the present invention has a multi-level pore structure of mesopores and macropores with a pore size range of 5-55nm, and has outstanding application performance in the positive electrode of lithium-sulfur batteries. At a high rate of 2C, the initial specific capacity of the lithium-sulfur battery is as high as 780.2-841.6mAh / g, and after 500 cycles, the capacity retention rate is 77.6-81.7%; at a high rate of 5C, the initial specific capacity is as high as 702.8-772.4mAh / g, indicating good high rate performance. The sulfur-host lithium-sulfur battery positive electrode material significantly improves the cycle life and rate performance of the lithium-sulfur battery and the specific capacity at high rate through the synergistic effect of the multi-level pore structure and the Mn3O4 / MnS homologous heterojunction structure, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction (XRD) diagrams of sulfur-host lithium-sulfur battery positive electrode materials obtained in Example 1 and Comparative Example 1;

[0025] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the sulfur-host lithium-sulfur battery cathode material obtained in Example 1;

[0026] Figure 3 This is a test diagram of the electrochemical cycle performance of the sulfur-host lithium-sulfur battery positive electrode material obtained in Example 1 at a 2C rate;

[0027] Figure 4 This is a high rate test diagram of the sulfur-host lithium-sulfur battery positive electrode material obtained in Example 1 at 0.1C-5C. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0029] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0030] In a specific embodiment of the present invention, the Joule heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0031] (1) Dissolve 0.3 mmol zinc nitrate hexahydrate in 10 mL methanol to prepare a 30 mM zinc nitrate methanol solution; dissolve 0.9 mmol 2-methylimidazole in 10 mL methanol to prepare a 90 mM 2-methylimidazole methanol solution; mix the zinc nitrate methanol solution and the 2-methylimidazole methanol solution, ultrasonically react at room temperature for 6 h, centrifuge, wash with methanol four times, and dry at 80° C. for 6 h to obtain a first precursor;

[0032] (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment six times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 900°C and a Joule heat treatment heating rate of 2000°C / s, to obtain a second precursor;

[0033] (3) 0.2 mmol of manganese chloride tetrahydrate was mixed with 10 mL of ethanol to prepare a 20 mM manganese chloride solution; 0.7 g of the second precursor was added to the above manganese chloride solution, and the mixture was stirred continuously at 80° C. until it was completely dried to obtain a third precursor;

[0034] (4) 0.1g of the third precursor and 0.5g of thioacetamide were placed on the left and right ends of the groove of the graphite sample stage of the Joule heating device, respectively, and Joule heat treatment was performed from room temperature to 800°C under a nitrogen protective atmosphere, with a heating rate of 2000°C / s, and the temperature was kept for 10s, and finally switched to an air atmosphere for cooling to room temperature, and the above Joule heat treatment was repeated 3 times to obtain a sulfur-hosted lithium-sulfur battery positive electrode material. Among them, the Joule heat treatment is to heat the room temperature to the target temperature under a nitrogen insulation atmosphere, then keep the temperature for reaction, and finally naturally cool to room temperature under an air atmosphere, which is represented as one time. Example 2

[0035] (1) Dissolve 0.2 mmol zinc nitrate hexahydrate in 10 mL methanol to prepare a 20 mM zinc nitrate methanol solution; dissolve 0.8 mmol 2-methylimidazole in 10 mL methanol to prepare an 80 mM 2-methylimidazole methanol solution; mix the zinc nitrate methanol solution and the 2-methylimidazole methanol solution, ultrasonically react at room temperature for 4 hours, centrifuge, wash with methanol three times, and dry at 60°C for 8 hours to obtain a first precursor;

[0036] (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment twice under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 1000°C and a Joule heat treatment heating rate of 1000°C / s, to obtain a second precursor;

[0037] (3) 0.1 mmol of manganese nitrate hexahydrate was mixed with 10 mL of ethanol to prepare a 10 mM manganese nitrate solution; 0.5 g of the second precursor was added to the above manganese nitrate solution, and the mixture was stirred continuously at 90° C. until it was completely dried to obtain a third precursor;

[0038] (4) 0.1g of the third precursor and 0.1g of thioacetamide were placed on the left and right ends of the groove of the graphite sample stage of the Joule heating device, and Joule heat treatment was performed from room temperature to 500°C under a nitrogen protective atmosphere, with a heating rate of 3000°C / s, and the temperature was kept for 15s. Finally, the temperature was cooled to room temperature under an air atmosphere, and the above Joule heat treatment was repeated 5 times to obtain a sulfur-hosted lithium-sulfur battery positive electrode material. Among them, the Joule heat treatment is to heat the room temperature to the target temperature under a nitrogen insulation atmosphere, then keep the temperature for reaction, and finally naturally cool to room temperature under an air atmosphere, which is represented as one time. Example 3

[0039] (1) Dissolve 0.4 mmol zinc nitrate hexahydrate in 10 mL methanol to prepare a 40 mM zinc nitrate methanol solution; dissolve 1.0 mmol 2-methylimidazole in 10 mL methanol to prepare a 100 mM 2-methylimidazole methanol solution; mix the zinc nitrate methanol solution and the 2-methylimidazole methanol solution, react with ultrasound at room temperature for 8 h, centrifuge, wash with methanol five times, and dry at 100 ° C for 4 h to obtain a first precursor;

[0040] (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment 10 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 800°C and a Joule heat treatment heating rate of 3000°C / s, to obtain a second precursor;

[0041] (3) 0.3 mmol of manganese chloride tetrahydrate was mixed with 10 mL of ethanol to prepare a 30 mM manganese chloride solution; 1.0 g of the second precursor was added to the above manganese chloride solution, and the mixture was stirred continuously at 60° C. to react until it was completely dried, thereby obtaining a third precursor;

[0042] (4) 0.1g of the third precursor and 1.0g of thioacetamide were placed on the left and right ends of the groove of the graphite sample stage of the Joule heating device, respectively, and Joule heat treatment was performed from room temperature to 1000°C in a nitrogen protective atmosphere, with a heating rate of 1000°C / s, and the temperature was kept for 5s, and finally switched to air atmosphere for cooling to room temperature, and the above Joule heat treatment was repeated once to obtain a sulfur-hosted lithium-sulfur battery positive electrode material. Among them, the Joule heat treatment is to heat the room temperature to the target temperature in a nitrogen insulation atmosphere, then keep the temperature for reaction, and finally naturally cool to room temperature in an air atmosphere, which is represented as one time. Example 4

[0043] (1) Dissolve 0.25 mmol zinc nitrate hexahydrate in 10 mL methanol to prepare a 25 mM zinc nitrate methanol solution; dissolve 0.9 mmol 2-methylimidazole in 10 mL methanol to prepare a 90 mM 2-methylimidazole methanol solution; mix the zinc nitrate methanol solution and the 2-methylimidazole methanol solution, ultrasonically react at room temperature for 5 h, centrifuge, wash with methanol four times, and dry at 80° C. for 6 h to obtain a first precursor;

[0044] (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment 8 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 850°C and a Joule heat treatment heating rate of 2000°C / s, to obtain a second precursor;

[0045] (3) 0.25 mmol of manganese chloride tetrahydrate was mixed with 10 mL of ethanol to prepare a 25 mM manganese chloride solution; 0.6 g of the second precursor was added to the above manganese chloride solution, and the mixture was stirred continuously at 80° C. to react until it was completely dried, thereby obtaining a third precursor;

[0046] (4) 0.1g of the third precursor and 0.4g of thioacetamide were placed on the left and right ends of the groove of the graphite sample stage of the Joule heating device, and Joule heat treatment was performed from room temperature to 900°C under a nitrogen protective atmosphere, with a heating rate of 1500°C / s, and the temperature was kept for 7s. Finally, the temperature was cooled to room temperature under an air atmosphere, and the above Joule heat treatment was repeated twice to obtain a sulfur-hosted lithium-sulfur battery positive electrode material. Among them, the Joule heat treatment is to heat the room temperature to the target temperature under a nitrogen insulation atmosphere, then keep the temperature for reaction, and finally naturally cool to room temperature under an air atmosphere, which is represented as one time. Comparative Example 1

[0047] The difference between Comparative Example 1 and Example 1 is that the heating device in step (4) is different, the Joule heating device is replaced with a tube furnace, and the other steps remain unchanged. The specific operation is as follows:

[0048] 0.1g of the third precursor and 0.5g of thioacetamide were placed in a tubular furnace and calcined under a nitrogen atmosphere, with a calcination temperature of 800°C, a heating rate of 5°C / s, and a heat preservation treatment of 10s. Finally, the temperature was cooled to room temperature under an air atmosphere, and the above calcination treatment was repeated 3 times to obtain a sulfur-host lithium-sulfur battery positive electrode material. Among them, the calcination treatment was heating the room temperature to the target temperature under a nitrogen heat preservation atmosphere, then keeping the temperature for reaction, and finally naturally cooling to room temperature under an air atmosphere, which was expressed as one time. Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 1 is that the heating devices in steps (2) and (4) are different, the Joule heating device is replaced with a tube furnace, and the other steps remain unchanged. The specific operation is as follows:

[0050] Step (2) operation: placing the first precursor in a tube furnace and calcining it under a nitrogen atmosphere at a calcination temperature of 900° C., a heating rate of 5° C. / s, and a calcination time of 2 h to obtain a second precursor;

[0051] Step (4) operation: 0.1 g of the third precursor and 0.5 g of thioacetamide are placed in a tubular furnace and calcined under a nitrogen atmosphere at a calcination temperature of 800°C, a heating rate of 5°C / s, and a heat preservation treatment of 10s. Finally, the temperature is switched to an air atmosphere to cool to room temperature. The above calcination treatment is repeated 3 times to obtain a sulfur-hosted lithium-sulfur battery positive electrode material. The calcination treatment is to heat the room temperature to the target temperature under a nitrogen atmosphere, then keep the temperature for reaction, and finally naturally cool to room temperature under an air atmosphere, which is represented as one time. Comparative Example 3

[0052] The difference between Comparative Example 3 and Example 1 is that in step (4), thioacetamide is not used, the atmosphere for heating, keeping and cooling during the Joule heat treatment is air, and the other steps remain unchanged. Comparative Example 4

[0053] The difference between Comparative Example 4 and Example 1 is that in step (4), the atmospheres for heating, keeping warm and cooling in the Joule heat treatment are all nitrogen, and the other steps remain unchanged.

[0054] Application Example 1

[0055] The sulfur-host lithium-sulfur battery positive electrode material obtained in Examples 1-4 and Comparative Examples 1-4 was used as the positive electrode of the lithium-sulfur battery, a polypropylene porous membrane (Celgard2300) was used as a separator, a lithium foil was used as a negative electrode, and an electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate and 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) was assembled into a button cell in a glove box protected by an inert atmosphere. The battery was subjected to electrochemical cycle performance test at 2C rate and high rate test at 0.1-5C on a CT-4008-5A6V system, and the test results are shown in Table 1.

[0056] The sulfur-host lithium-sulfur battery positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to a nitrogen full adsorption test (N2-BET) pore size distribution test. The test results are shown in Table 1, wherein the N2-BET pore size distribution test results are full pore size distributions based on the NLDFT model.

[0057]

[0058] As shown in Table 1, the use of tubular furnace calcination and Joule heating device will affect the pore size and the presence of MnS. The tubular furnace has a relatively slow cooling rate, which causes MnS to be completely oxidized in an air atmosphere. The Joule heating device has a fast heating and cooling rate, which can achieve partial oxidation of MnS. At the same time, the Joule heating device has a greater impact on the pore size of the material. Therefore, the performance (capacity, cycle) of the material treated by the Joule heating device is more superior; Thioacetamide is the key to the formation of Mn3O4 and MnS. In the Joule heat treatment, the atmosphere for heating, heat preservation and cooling is all in the air atmosphere to obtain Mn3O4. The electrochemical performance of Mn3O4 itself The electrochemical performance of MnS itself is not good, and the electrochemical effect is good only when it co-exists with MnS, and Mn3O4 and MnS have a synergistic effect; switching to air atmosphere during the cooling process is the key to the formation of Mn3O4, and the atmosphere for heating, insulation and cooling in Joule heat treatment is nitrogen atmosphere to obtain MnS. The electrochemical performance of MnS itself is not good, and the electrochemical effect is good only when it co-exists with Mn3O4, and Mn3O4 and MnS have a synergistic effect; in addition, the pore size will also affect the electrochemical performance, and the multi-level pore (mesopore, macropore) carbon material structure and the heterojunction structure of Mn3O4 and MnS jointly affect the electrochemical performance of lithium-sulfur batteries.

[0059] Figure 1 The X-ray diffraction (XRD) diagram of the sulfur-host lithium-sulfur battery positive electrode material obtained in Example 1 and Comparative Example 1. It can be seen from the figure that the sulfur-host lithium-sulfur battery positive electrode material of Example 1 is mainly composed of two phases, Mn3O4 and MnS, while Comparative Example 1 is mainly composed of Mn3O4. This is mainly due to the difference in cooling speed. Using a Joule heat heating device, it only takes about 1 minute to cool from 750°C to 50°C, so that MnS is only partially oxidized. Using a tubular furnace for heating, it takes about 3 hours to cool from 750°C to 50°C. The cooling rate is slow, and MnS has sufficient time to be completely oxidized in the air atmosphere to form Mn3O4.

[0060] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the sulfur-host lithium-sulfur battery cathode material obtained in Example 1. It can be seen from the image that Mn3O4 and MnS nanocrystals form a heterogeneous structure.

[0061] Figure 3The electrochemical cycle performance diagram of the sulfur-host lithium-sulfur battery positive electrode material obtained in Example 1 at a 2C rate. It can be seen from the figure that the sulfur-host lithium-sulfur battery positive electrode material shows a first-cycle discharge of 841.6 mAh / g. After 500 cycles, the capacity remains at 687.3 mAh / g, the average capacity decay rate per cycle is 0.0037%, and the capacity retention rate is 81.7%. Combined with the data shown in Table 1, compared with Example 1, Comparative Examples 1-4 show poor cycle stability and higher capacity decay rate under the same conditions. The main reasons for this performance advantage are as follows: (1) ZIF-8 (carbon material) is prepared from zinc nitrate and 2-methylimidazole, and then ZIF-8 is subjected to Joule heating to obtain a ZIF-8-derived porous carbon material. The material has a high specific surface area and a rich multi-level pore structure, which is not only conducive to the efficient loading of sulfur, but also can significantly improve the conductivity of the positive electrode; in addition, ZIF-8 as a carrier increases the dispersibility of metal compounds (Mn3O4 and MnS), exposing more active sites; (2) Compared with Comparative Examples 1-4, In comparison, comparative examples 1-4 respectively obtained carbon materials of Mn3O4, carbon materials of Mn3O4, carbon materials of Mn3O4, and carbon materials of MnS, and embodiment 1 obtained Mn3O4 / MnS heterostructure carbon materials. The Mn3O4 / MnS heterostructure of the sulfur-host lithium-sulfur battery positive electrode material in embodiment 1 further created a highly active interface, which can enhance the chemical adsorption and catalytic conversion of polysulfides, thereby significantly promoting the kinetic process of sulfur redox reaction and improving the overall performance of the lithium-sulfur battery.

[0062] Figure 4 The figure is a high rate test diagram of the sulfur-host lithium-sulfur battery positive electrode material obtained in Example 1 at 0.1-5C. It can be seen from the figure that the sulfur-host lithium-sulfur battery positive electrode material can achieve a specific capacity of 772.4mAh / g at a high charge and discharge rate of 5C, showing good rate performance; at the same time, at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, and 5C, it reaches 1052.5mAh / g, 980.5mAh / g, 915.8mAh / g, 900.5mAh / g, 841.6mAh / g, 810.7mAh / g, and 772.4mAh / g, respectively, and then the capacity is restored to 1000.8mAh / g after switching to 0.1C at a current density of 5C, and the capacity recovery rate reaches 95.1%, indicating that the sulfur-host lithium-sulfur battery positive electrode material has highly reversible electrochemical properties.

[0063] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for rapidly preparing a sulfur-host lithium-sulfur battery cathode material, characterized in that: The following steps are involved: (1) Mixing a zinc nitrate methanol solution and a 2-methylimidazole methanol solution, subjecting the mixture to ultrasonic reaction at room temperature for 4-8 hours, and then centrifuging, washing, and drying to obtain a first precursor; (2) placing the first precursor in a groove of a graphite sample stage of a Joule heating device, and performing Joule heat treatment under a nitrogen protective atmosphere to obtain a second precursor; (3) mixing a manganese source with ethanol to prepare a manganese-containing solution; adding the second precursor to the manganese-containing solution, stirring and reacting at 60-90° C. until completely dried, to obtain a third precursor; (4) placing the third precursor and thioacetamide at the left and right ends of the groove of the graphite sample stage of the Joule heating device, respectively, and performing a Joule heat treatment of increasing the temperature under a nitrogen protective atmosphere. After reaching the target temperature, the temperature is kept for 5-15 seconds, and then the temperature is switched to an air atmosphere for a Joule heat treatment of decreasing the temperature, thereby obtaining a sulfur-host lithium-sulfur battery positive electrode material; In the step (2), the Joule heat treatment temperature is 800-1000°C, the heating rate is 1000-3000°C / s, and the number of Joule heat treatments is 2-10 times; In the step (3), the manganese source is manganese chloride tetrahydrate or manganese nitrate hexahydrate; the concentration of the manganese-containing solution is 10-30 mM; the amount of the second precursor added is 0.5-1 g:10 ml based on the amount of ethanol in the manganese-containing solution; In the step (4), the usage ratio of the third precursor to thioacetamide is 0.1 g: 0.1-1 g; the Joule heat treatment conditions are: heat treatment temperature 500-1000°C, heating rate 1000-3000°C / s, and Joule heat treatment times 1-5 times.

2. The rapid preparation method of sulfur-host lithium-sulfur battery positive electrode material according to claim 1, characterized in that: In the step (1), the concentration of the zinc nitrate methanol solution is 20-40 mM, and the concentration of the 2-methylimidazole methanol solution is 80-100 mM.

3. The rapid preparation method of sulfur-host lithium-sulfur battery positive electrode material according to claim 1, characterized in that: Furthermore, in the step (1), the washing conditions are: washing with methanol three to five times; and the drying conditions are: drying temperature 60-100° C., and drying time 4-8 h.

4. An application of a sulfur-host lithium-sulfur battery positive electrode material prepared by the preparation method according to any one of claims 1 to 3, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method for cathode material of lithium-sulfur battery

    CN109309217A

  • Zeolite-imidazole-framework derived nitrogen-doped hierarchical porous carbon@trimanganese tetroxide@carbon / sulfur and preparation method and application thereof

    CN110600690A

  • Metal oxide-metal sulfide heterojunction material and preparation method and application thereof

    CN115084480A

  • Lithium ion battery cathode material zinc manganate nanorod and preparation method thereof

    CN108400324A

  • Lithium-sulfur battery positive host material as well as preparation method and application thereof

    CN111463413A